Tờ trình Về Điều chỉnh Quy hoạch chung Thủ đô Hà Nội đến năm 2045, tầm nhìn đến năm 2065 - Thủ tướng Chính phủ (2024)
Toàn văn Tờ trình Về Điều chỉnh Quy hoạch chung Thủ đô Hà Nội đến năm 2045, tầm nhìn đến năm 2065.